Bryophytes - Sabovljević, Marko S.; Sabovljević, Aneta D. (IntechOpen, 2020)
Bryophytes, a group of plants present in all terrestrial biomes of the Earth, play a significant role in ecosystems and have potential use in many life domains. They can be used in the cosmetic, pharmaceutical, and healthcare domains and can help to improve air quality, create bio-repellents and bio-pesticides, and help cure both human and animal diseases. This book discusses novel aspects of fundamental and applicative bryophyte biology.